2022
DOI: 10.2147/jir.s342503
|View full text |Cite
|
Sign up to set email alerts
|

GIMAP7 as a Potential Predictive Marker for Pan-Cancer Prognosis and Immunotherapy Efficacy

Abstract: Background: GIMAP, a GTP enzyme of immune-related proteins, plays a crucial role in immune mechanisms. Investigating GIMAP7 expression in pan-cancer can provide efficient guidance for predicting clinical prognosis and identifying novel immunotherapy targets. Methods: Gene expression in different tumour types and stages was analysed based on The Cancer Genome Atlas and the Genotype-Tissue Expression database. An immunohistochemical assay was used to explore the differences in GIMAP7 protein levels in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…These prior studies support our finding that GIMAP7 could be important in severity given its presence on the surface of T-lymphocytes [51]. In the time since GIMAP7 was initially identified [52], it has subsequently been shown to be a potential marker for various cancer types, which further supports its immune-related role [53][54][55][56]. Although the underlying mechanism for this protein is yet to be characterized, we are not surprised by its role in other immune-related diseases or in SARS-CoV-2 disease severity.…”
Section: Discussionsupporting
confidence: 87%
“…These prior studies support our finding that GIMAP7 could be important in severity given its presence on the surface of T-lymphocytes [51]. In the time since GIMAP7 was initially identified [52], it has subsequently been shown to be a potential marker for various cancer types, which further supports its immune-related role [53][54][55][56]. Although the underlying mechanism for this protein is yet to be characterized, we are not surprised by its role in other immune-related diseases or in SARS-CoV-2 disease severity.…”
Section: Discussionsupporting
confidence: 87%
“…The immune system is essential in control of tumors, and effective immunotherapy could be achieved through preexisting adaptive immune responses within tumors, such as checkpoint inhibitors (Bruni et al, 2020a). In view of the prevalence of tumors and the convoluted process of tumorigenesis, it is of great significance to explore in-depth the expression of relevant genes in pan-cancer and to assess their levels for clinical treatment and prognostic prediction (Qin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GABRD gene may be a prognostic marker in gliomas with low expression, and it is associated with poor prognosis [ 10 , 11 ]. In another study, GABRD expression was found to be significantly lower in IDH wild-type diffuse gliomas compared to IDH mutant tumors [ 12 ], and patients with high GABRD expression had a better prognosis than those with low GABRD expression [ 13 ]. Taken together, it is suggested that the functional mechanism of GABRD in cancer needs to be investigated on specific cancer types.…”
Section: Introductionmentioning
confidence: 99%